2015
DOI: 10.1111/apm.12423
|View full text |Cite
|
Sign up to set email alerts
|

Lipoarabinomannan‐specific TNF‐α and IFN‐γ as markers of protective immunity against tuberculosis: a cohort study in an endemic setting

Abstract: Lipoarabinomannan (LAM) is a virulent factor used for entry and survival of Mycobacterium tuberculosis (Mtb) in macrophages. Although the role of LAM for the diagnosis of tuberculosis (TB) has been extensively investigated, its cytokine response during natural Mtb infection in humans is largely unknown. In this study, LAM-specific IFN-γ, TNF-α, and IL-10 levels following whole blood assay were measured in untreated pulmonary TB patients, their contacts and community controls at baseline. In treated patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…In agreement with our observation, a study in Brazil has reported that IFN-c response to the 38 KDa/CFP-10 showed an increasing tendency in treated TB patients (12). Although we have reported a similar observations in the levels of IFN-c against recombinant HBHA (20), Rv2031 (21), and LAM (23), this is the first report from cohort study to show that Mtb suppresses the production of IFN-c against the 38 kDa during Mtb infection or clinical TB. Earlier studies in the murine model (11,29,30) have shown that the 38-kDa antigen is a potent inducer of T-cell immunity.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In agreement with our observation, a study in Brazil has reported that IFN-c response to the 38 KDa/CFP-10 showed an increasing tendency in treated TB patients (12). Although we have reported a similar observations in the levels of IFN-c against recombinant HBHA (20), Rv2031 (21), and LAM (23), this is the first report from cohort study to show that Mtb suppresses the production of IFN-c against the 38 kDa during Mtb infection or clinical TB. Earlier studies in the murine model (11,29,30) have shown that the 38-kDa antigen is a potent inducer of T-cell immunity.…”
Section: Discussionsupporting
confidence: 92%
“…However, the level of IFN‐γ against HBHA was significantly higher in HHCs and CCs than untreated patients . Similarly, the level of IL‐10 against ESAT‐6/CFP‐10 , HBHA , and LAM was significantly higher in untreated PTB patients than in CCs, while IL‐10 against Rv2031 was the highest in CCs compared with untreated patients and HHCs.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations